Osseointegrated implants in maxillary sinus-lift and bone graft areas - Camila Daher Cozac; Adérico Santana Guilherme; José Everaldo de Aquino Souza; Arioldo Teles de Castro; Cinthia Almeida Barros; Ricardo Alexandre Zavanelli; José Marcos Alves Fernandes; Verônica Araújo dos Santos
Objectives: To assess the satisfaction index of such treatment; provide statistical data about this index and explain to the dental community, the possible satisfaction expressed by the group assisted, with regard to the intervention performed. Methods: After applying the questionnaire, the the values of the analysis obtained were tabulated and statistical calculation was then applied(Fisher Exact test and Chi-Square test) with a significance level of 5% (p <0.05). Results: According to the data obtained, it was found that the degree of satisfaction of nonsmoker patients was significantly higher than that of the group of smokers, irrespective of their economic condition. As regards gender, the satisfaction index of women showed a higher percentage than that of men. In this study, the need for additional surgery, the loss of bone graft and repetition of the surgical procedure did not occur frequently. All patients were satisfied with the surgery performed, and the majority did not need additional surgery. Conclusion: In view of the factors evaluated in this study, it could be concluded that a significant portion of patients attended by the Improvement and Specialization Courses in Implant Dentistry at the Faculty of Dentistry, Federal University of Goiás, as from the year 2004, reported that the osseointegrated implant placement techniques and bone graft procedures are considered traumatic, but nevertheless they experienced a significant improvement in their quality of life after treatment.